A very persistent chicken bone: two separate perforations from the same foreign object 2 months apart. Issue 5 (15th May 2019) - Brown, Andrew James; Whitehead-Clarke, Thomas; Tudyka, Vera
Abstract : A 56-year-old man presented acutely with abdominal pain and raised inflammatory markers. Initial CT images demonstrated acute inflammation in the right upper quadrant surrounding a high-density linear structure. The appearance was of a chicken bone causing a contained small bowel perforation. This was managed conservatively with intravenous antibiotics and the patient was discharged 10 days later. The same patient returned to the hospital 2 months later, once again with an acute abdomen. CT imaging on this occasion showed distal migration of the chicken bone as well as free gas and fluid indicative of a new small bowel perforation. The patient underwent an emergency laparotomy, washout and small bowel resection. No foreign body was found at laparotomy or in the histopathology specimen. The postoperative course was complicated by an anastomotic leak. A further CT on that admission demonstrated that the chicken bone had migrated to the rectum!